A comparative analysis of the architectural lighting systems in selected problem areas of hotels, Century Park Sheraton and Philippine Plaza,in Manila - Asinobi, Jonathan Chukwuemeka Nwabuaze (1987)
The fulcrum of this study is actually a product of vision or seeing process. Vision in relation to the brain has chiefly lead to man's insatiable habits, of changing and desiring to change the position of things and their nature. Nature, a world of mystery and majesty dominated by man; his constant sensational bombardment and bewildering anarchy of wishes and wants, that things in them trend to his desire; Yet, the world he never crated. Man's perception of his environment and his numerous desires to change his space are things of unrealistic imaginations as nature has since ages stood still, indifferent and recalcitant to effects of human perception. This is one aspect where human perception has failed otherwise the earth should have long been into visisble motion. Science and nature have been identified man as piece of living organism with considerable abilities. It is therefore required of any systematic devices intending to render services to man, (mechanical, computer units or even "man as a meter" for instance, in service to his fellowmen) are all expected to be oriented to one agreeable fact; "that the ordinary man has the ability to take decision relative to his taste or wants." He has the ability to appreciate nature and admire forms. Vision interpreted by the brain has chiefly lead to man's continous evaluation and awareness of his environment. Architecture has provided built spaces for human utilization. It is expected that the architectural whole, say in a hotel building should meet with users requirements. However strong perception and understanding from the part of the designer are required to truly provide a comfortable, safe and therefore relaxing visual environemnt. This is an architectural metaphor which lighting and lighting designers are required to complete. In comparing the two separate environments of this study entitled, "A Comparative Analysis of Architectural Ligthing Systems in Selected Problem Areas of Hotels, Century Park, Sheraton and Philippine Plaza", in Manila, it was born in mind that what was vital is the means and how to achieve practical lighting solutions which would foremost consider safety and comfort of the users. This was executed in the best of lighting concepts, but guided by a principal theory in the study - "lighting design should be practical." In evaluating the selected problem areas of the hotels and upholding the guiding theory of the report, the designer saw the need of carefully configurating emotional theories and related orthodox approaches as the best guarantte for healthy lighted environment.